(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article discusses the importance of using experimental problems in the methodology of teaching physics at a technical university. At the beginning of the 21st century, the well-being and further prosperity of the republic depend on scientific and technological progress and the intellectual potential of the country. In this regard, from the first day the Republic of Uzbekistan gained independence, the President and the country’s leadership put the issue of education among the highest priorities.